2021
DOI: 10.22547/ber/13.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Is Gold a Hedge and Safe Haven during Political Uncertainties?

Abstract: Technological advancements not only bolstered almost all activities, but also accelerated the spread of information in blinks. Thus, announcements about market volatilities along with subpar financial instruments’ performance have led investors to search for alternative assets to cope with amplified uncertainties. Investors in politically unstable economies, like Pakistan, are more prone to the risks of uncertainties so require some safe investments. Previously gold has been investigated as a hedge and safe ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Different public policy instruments affect the economy in different ways, but among all these, the changes in tax rates have quite different effects. Various studies have reported the relationship between economic growth and the revenue policies of the government (Anastassiou & Dritsaki, 2005;Muriithi, 2013;Rasheed, Ahmad, & Javid, 2021b;Stoilova & Patonov, 2013). Ferede & Dahlby (2012) investigated the relationships between income tax rates, private investments, and economic growth.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Different public policy instruments affect the economy in different ways, but among all these, the changes in tax rates have quite different effects. Various studies have reported the relationship between economic growth and the revenue policies of the government (Anastassiou & Dritsaki, 2005;Muriithi, 2013;Rasheed, Ahmad, & Javid, 2021b;Stoilova & Patonov, 2013). Ferede & Dahlby (2012) investigated the relationships between income tax rates, private investments, and economic growth.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The ARDL bounds test was developed by Pesaran, Shin, & Smith (2001) and is used to investigate the long-term relationship among variables. It provides a better indication of the long-run relationship compared to traditional cointegration testing (Rasheed & Tahir, 2012) and has several advantages comparatively (Rasheed et al, 2021b). It…”
Section: Ardl (Autoregressive Distributed Lag) Approachmentioning
confidence: 99%